2018
DOI: 10.1002/bem.22154
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electromagnetic fields on cultured human retinal pigment epithelial cells

Abstract: A great deal of evidence has confirmed that electromagnetic fields (EMFs) can affect the central nervous system. In this study, cultured neonatal human retinal pigment epithelial (hRPE) cells were exposed to pulsed EMF of 1 mT intensity and 50 Hz frequency 8 h daily for 3 days. In addition to cell proliferation and cell death assays, immunocytochemistry for RPE65, PAX6, nestin, and cytokeratin 8/18 proteins were performed. Real-time reverse transcriptase polymerase chain reaction (RT-PCR) was performed for NES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Evidence has confirmed that electromagnetic frequency impacts the central nervous system, and the degree of electromagnetic hypersensitivity symptoms varies among humans. It is postulated that the overall OSS of an individual may contribute to the ability to manage reactive oxygen species precipitated by electromagnetic frequency exposure (Nasrabadi et al, 2018).…”
Section: Electromagnetic Fields and The Eyes And Bloodmentioning
confidence: 99%
“…Evidence has confirmed that electromagnetic frequency impacts the central nervous system, and the degree of electromagnetic hypersensitivity symptoms varies among humans. It is postulated that the overall OSS of an individual may contribute to the ability to manage reactive oxygen species precipitated by electromagnetic frequency exposure (Nasrabadi et al, 2018).…”
Section: Electromagnetic Fields and The Eyes And Bloodmentioning
confidence: 99%
“…[24][25][26] Many investigations have demonstrated the effects of ELF-PEMFs on the apoptosis, proliferation, differentiation, angiogenic and metastatic properties of different cells. [27][28][29] This study aimed to determine the ELF-PEMF effects on the angiogenic factors in human RPE (hRPE) cells in different exposure times.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many investigations have focused to modify the miRNA functions in cancer cells to achieve therapeutic approaches. In this regard, it was demonstrated that natural compounds like polyphenols, curcumin, resveratrol, silibinin, and quercetin can suppress oncogenes or stimulate tumor suppressor genes by altering miRNA expressions …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it was demonstrated that natural compounds like polyphenols, curcumin, resveratrol, silibinin, and quercetin can suppress oncogenes or stimulate tumor suppressor genes by altering miRNA expressions. [12][13][14][15][16][17] Quercetin is a polyphenol compound and the most abundant flavonoid in various fruits, flowers, and medicinal herbs. Quercetin beneficial effects such as antioxidant, anti-inflammatory, antimicrobial, and antitumor activities are well documented.…”
Section: Introductionmentioning
confidence: 99%